25 IDENTIFICATION OF PATHOGENIC BACTERIA IN SEVERE CROHN'S DISEASE. (7th February 2019) - Rodriguez-Palacios, Alexander; Conger, Mathew; Hopperton, Austin; Ezeji, Jessica C; Erkkila, Hailey L; Fiocchi, Claudio; Cominelli, Fabio
Abstract: Background: Despite great advancements in therapy, it remains unclear why inflammation in the digestive system of patients suffering Crohn's Disease (CD) is progressive and leads to complications (e.g., enteric fistulas) that are only alleviated by surgical removal of the damaged bowel. By using a three-dimensional profiling method, we recently discovered that surgically removed CD bowels have complex 3D-networks of microscopic lesions that follow principles of 'geological caverns'. Because such lesions contain purulent debris (pus), inflammatory cells, and bacterial DNA, their collective presence with that of bacteria could explain CD progression and recurrence. The main objective of this study was to use standard and novel culture methods to determine if bacteria previously identified by DNA methods can be found alive in such microscopic cavernous fistulous tract lesions (CavFT) and could induce intestinal inflammation in mice prone to CD (SAMP1/YitFc). Methods: Stereomicroscopic samples from the ileum from 5 CD patients undergoing surgery were obtained under strict aseptic conditions for incubation of anaerobic bacteria. Transplantation experiments of purulent debris and of pure bacterial isolates were conducted in adult (55-wk-old) and young (6-week-old) germ-free SAMP mice to determine acute and chronic intestinal inflammatory responses and gut microbial growth dynamics. In vitro growth assays were conducted to determine the effect of oxygen exposure on bacterial viability, inhibition, and resilience. Single colony 16S rRNA gene Sanger sequencing was used for bacterial speciation. Results: A remarkable array of viable, and cultivable bacteria from the dissected CavFT lesions were revealed from the ilea of CD patients that underwent surgery, but not from paired control mucosa samples. All isolates, with one exception (e.g., Enterococcus faecalis ) were strict anaerobes, with a predominance of Bacteroidetes (e.g., compared to Clostridium, 6:1 ratio). Among the Bacteroidetes, Parabacteroides distasonis was present in two patients that exhibited a consistent pattern of pro-inflammatory activity in SAMP mice (3D-cobblestone formation, histological inflammation), when compared to Alistipes finegoldii and Lactobacillus salivarius, which was present as a dominant microbe in mucosal ulcers of a colonic CD. P. distasonis, deemed a slow-growing bacterium, survived prolonged exposure to oxygen (room air), showed the ability to invade the gut wall of germ-free SAMP mice, and stimulate the growth of other specific CavFT bacteria in vitro. Conclusions: Findings support that bacteria inhabiting CavFT in CD could play a perpetuating pathogenic role in CD, by initiating liquefactive 'sinkhole' lesions on mucosal surfaces, and by perpetuating microscopic 'cavernous fistulous tract' lesions in deep gut muscle layers, which could lead to chronic fistulas.